Pemanfaatan Framework React Native dalam Pengembangan Aplikasi Pemesanan Minuman Kopi pada Kedai Bycoffee - Adlan Husein Malahella; Issa Arwani; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Kedai ByCoffee is a business engaged in the field of F&B providers in the city of Malang. ByCoffee provides many types of coffee drinks. As a business that operates in the sector of F&B, the quality of service is very important. The quality of service at this ByCoffee shop is still very manual and less practical. Taking advantage of technological advances can facilitate the service process, such as by making an application for ordering coffee drinks available at the store. Therefore, in this thesis a coffee drink ordering application was built at the ByCoffee coffee shop by using the React Native framework which is expected to simplify and speed up the service process at the ByCoffee shop. In its development, the application of ordering coffee drinks at the ByCoffee shop was designed using UML and implemented using the React Native framework, and Javascript programming language. After the system is finished, proceed with testing using functional testing and non-functional testing. Functional testing is done by trying all the features that have been determined at the beginning with the path that has been determined, and the results are all features can function properly. Non-functional testing is done by conducting usability testing using the System Usability Scale method, and compatibility testing. The test results show that the application of ordering coffee drinks at the ByCoffee shop has been able to meet the needs of non-functional well.